'Self' and the modernist city - Pizzi, Katia (Primerjalna književnost, 2004)
Trieste has traditionally suffered the status of a border city. This border has been experienced as a source of permanent anxiety and displacement, acquiring the status of a chronotope in the Bakhtinian sense. The city's eccentric position has frequently resulted in Trieste being personified or emerging as an overwhelming presence in its literature. Local authors have experienced the city "from within", as superimposed, "merged" with their "Selves". My discussion includes the canonic author Italo Svevo and focuses in particular on the contemporary Stelio Mattioni and his novel Il richiamo di Alma (1980).
Keywords: self; Svevo, Italo, 1861-1928; Trst; Mattioni, Stelio, 1921-1997; italijanska književnost; novel; roman